2009
DOI: 10.1002/pbc.21977
|View full text |Cite
|
Sign up to set email alerts
|

Detection of CpG island hypermethylation of caspase‐8 in neuroblastoma using an oligonucleotide array

Abstract: A significant difference in the methylation status within the CpG island of CASP8 was shown between favorable and unfavorable subtypes, and CASP8 methylation detected by oligoarray may be useful in the clinical evaluation of neuroblastomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Since decreased expression of caspase 8 is a recurrent event in NB [18] , we tested whether CASP8 SNP D302H could affect the expression of caspase 8. We measured caspase 8 mRNA expression in two independent cohorts of NB tumor samples.…”
Section: Resultsmentioning
confidence: 99%
“…Since decreased expression of caspase 8 is a recurrent event in NB [18] , we tested whether CASP8 SNP D302H could affect the expression of caspase 8. We measured caspase 8 mRNA expression in two independent cohorts of NB tumor samples.…”
Section: Resultsmentioning
confidence: 99%
“…Most commonly in NB as well as other cancers, casp8 repression is a result of hypermethylation at CpG islands within the CASP8 promoter region [117,121,123]. Methylation of the promoter region regulates casp8 expression thus allowing, based on cellular conditions and signaling, for casp8 re-expression.…”
Section: Discussionmentioning
confidence: 99%
“…Teitz et al and others have demonstrated that casp8 is preferentially silenced in NB cell lines and patient samples though rarely deleted [17,[115][116][117]. Loss of casp8 has also been shown in other tumors including small cell lung carcinoma, rhabdomyosarcoma, glioblastoma, retinoblastoma, medulloblastoma, Wilms tumors and colorectal carcinomas [118][119][120][121][122][123].…”
Section: Caspase-8 In Cancermentioning
confidence: 99%
See 2 more Smart Citations